Attracting And Maintaining Valuable Employees in Modern Organizations: An Analysis of Selected Methods - Anna KOCHMAŃSKA (Communications of International Proceedings, 2022)
The key to success of modern companies are employees with their knowledge and competencies. The art is to attract such employees who have not only highly developed competencies, both soft and hard, but also whose system of values is consistent with the system of values, which is professed by the organization. Moreover, in order for them to stay with the organization for a longer period of time, it must provide them with favorable conditions for this. The main aim of this article is not only to present selected selection methods that make it possible to precisely verify the competency profile of potential job candidates, but also to indicate important determinants that influence the employees' staying in the company for longer. The article provides a basis for further empirical research concerning employees' evaluation of organizational conditions which influence their feeling of identification with the company.
Keywords: Employee selection; adaptation to new organizational conditions; innovative training; career